2017
DOI: 10.3892/ol.2017.7366
|View full text |Cite
|
Sign up to set email alerts
|

TT‑1, an analog of melittin, triggers apoptosis in human thyroid cancer TT cells via regulating caspase, Bcl‑2 and Bax

Abstract: Abstract. Melittin is a 26 amino acid residue antimicrobial peptide with known antitumor activity. In the present study, a novel peptide TT-1, derived from melittin and contained only 11 amino acids, was designed, and its antitumor effect was investigated. The present study is aimed to elucidate the effects and relative mechanisms of TT-1 on a human thyroid cancer cell line (TT) in vitro and in vivo. Cell viability assays, Annexin V/propidium iodide assays, western blotting and quantitative reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…1). The apoptotic rates of human thyroid cancer cell line (TT) cells were increased following melittin treatment, melittin causes increased Caspase3, Caspase9, Bax, and inhibited B-cell lymphoma 2 genes, and protein expression (Wan 2018). Melittin decreased the invasion rate of MCF-7 human breast cancer cell line by down-regulating CD147, and MMP-9 by inhibiting cyclophilin A expression so the results provide evidence for melittin in anticancer therapy, and mechanisms (Wang et al 2017).…”
Section: Discussionmentioning
confidence: 79%
“…1). The apoptotic rates of human thyroid cancer cell line (TT) cells were increased following melittin treatment, melittin causes increased Caspase3, Caspase9, Bax, and inhibited B-cell lymphoma 2 genes, and protein expression (Wan 2018). Melittin decreased the invasion rate of MCF-7 human breast cancer cell line by down-regulating CD147, and MMP-9 by inhibiting cyclophilin A expression so the results provide evidence for melittin in anticancer therapy, and mechanisms (Wang et al 2017).…”
Section: Discussionmentioning
confidence: 79%
“…11), the administration of Melittin loaded niosome shows the synergic and higher up-regulating effects in (Bax, Caspase3 and Caspase9 genes) and downregulating (Bcl2, MMP2, and MMP9 genes) in both cell lines.The apoptotic rates of human thyroid cancer cell line (TT) cells were increased following Melittin treatment, Melittin causes increased Caspase3, Caspase9, Bax, and inhibited B-cell lymphoma 2 genes and protein expression[59].Melittin decreased the invasion rate of MCF-7 human breast cancer cell line by down-regulating CD147 and MMP-9 by inhibiting cyclophilin A expression so the results provide an evidence for Melittin in anticancer therapy and mechanisms[60].Honey bee venom contain Melittin and chrysin are effective for destroying chemoresistant ovarian cancer cells through upregulation of Caspase3 and Caspase9 and down-regulation of Bcl2 genes expression[61].…”
mentioning
confidence: 99%
“…Huang [ 22 ] reported that SIO induced the death of prostate cancer cells (DU-145, PC-3, and LNCaP) and showed an increase in the Bax/Bcl-2 ratio. Furthermore, Wan et al [ 28 ] found that an oligopeptide (KIKAVLKVLTT) derived from melittin induced the death of thyroid cancer TT cells via upregulation of Bax and down-regulation of Bcl-2. Our results also indicated that PAP induced apoptosis of H1299 cells by up-regulating the Bax/Bcl-2 ratio, which was consistent with previous studies.…”
Section: Resultsmentioning
confidence: 99%